Pengembangan Media Pembelajaran Komik Digital Berbasis Smartphone untuk Siswa Sekolah Dasar - Syahmi, Favian Avila; Ulfa, Saida; Susilaningsih, Susilaningsih (Universitas Negeri Malang, 2022)
This research and development aims to produce a product in the form of digital comic learning media as a learning innovation in social studies subjects, the material for the collapse of the kingdom of Kediri. Research Research and Development (R & D) using the Borg and Gall stages according to the needs of developers and in accordance with the product (search and data collection; planning, developing products, test the feasibility of the product, the revision of the results of the feasibility test products, field testing and refinement of the product) . In learning digital comics, this is a complement to social studies learning, which means that the media is intended to complement the learning material that students receive in the classroom. Use of this media in learning must use a smartphone. The feasibility of the product that has been carried out by experts and students has received a positive response. So it can be said that the digital comic media material for the fall of the Kediri kingdom is suitable for use in classroom learning. This media provides convenience, attractiveness, and motivation in teaching and learning activities, so that students' desire to learn about social studies learning will increase.AbstrakPenelitian dan pengembangan ini bertujuan untuk menghasilkan suatu produk yang berupa media pembelajaran komik digital sebagai suatu inovasi pembelajaran pada mata pelajaran IPS materi runtuhnya kerajaan Kediri. Penelitian Research and Development (R&D) menggunakan metode Borg and Gall yang tahapannya sesuai dengan kebutuhan pengembang dan sesuai dengan produk (pencarian dan pengumpulan data; perencanaan, mengembangkan produk, uji kelayakan produk, revisi hasil uji kelayakan produk, uji coba lapangan dan penyempurnaan produk). Didalam pembelajaran komik digital ini menjadi pelengkap dalam pembelajaran IPS, yang berarti media ditujukan untuk melengkapi materi pembelajaran yang diterima siswa didalam kelas. Media ini penggunaanya dalam pembelajaran harus menggunakan smartphone. Kelayakan produk yang telah dilakukan oleh para ahli dan siswa mendapatkan hasil tanggapan positif. Sehingga dapat dikatakan bahwa media komik digital materi runtuhnya kerajaan kediri ini layak digunakan didalam pembelajaran dikelas. Media ini memberikan kemudahan, kemenarikan, dan motivasi dalam aktivitas belajar mengajar, sehingga siswa rasa ingin belajar terhadap pembelajaran IPS akan meningkat.